The relationship between customer satisfaction, brand trust and brand loyalty - Daffa Akhila; Thamrin Thamrin (Universitas Negeri Padang, 2022)
The purpose of this study is to analyze satisfaction and brand trust on brand loyalty at Rimbun Coffee coffee shop with brand love as moderating. The type of this research is quantitative research. The population in this study are customers who have tested the Rimbun Coffee coffee shop in Padang City with a sample of 140 respondents. The analysis of this study uses SmartPLS 3.0. The results of this study indicate: (1) Satisfaction has a positive effect on Rimbun Coffee's brand loyalty. (2) Brand trust has a positive and significant effect on brand loyalty felt by Rimbun Coffee coffee shop customers in Padang City. (3) Brand love significantly moderates the relationship between satisfaction and Rimbun Coffee's brand loyalty so that it has an impact on Rimbun Coffee's customers. (4) Brand love significantly moderates the relationship between brand trust and Rimbun Coffee's brand loyalty.